Relative long-term survival in out-of-hospital cardiac arrest: Is it really improving? - Majewski, David; Ball, Stephen; Bailey, P.; Bray, Janet; Finn, Judith (ELSEVIER IRELAND LTD, 2020)
Aim: To describe the long-term survival of out-of-hospital cardiac arrest (OHCA) patients and to determine whether survival is improving in comparison to the general age- and sex-matched population. Methods: We utilised the St John Western Australia (WA) OHCA database to retrospectively identify patients aged ≥16 years who experienced an OHCA within the Perth metropolitan area between 1998 and 2017 and survived for at least 30-days post arrest. Patients were excluded if their primary residence was not WA, they did not have an emergency medical services attempted resuscitation (or bystander defibrillation) or did not have an arrest of medical aetiology. Relative survival ratios stratified by decade of arrest were calculated by dividing observed survival of the study cohort by the expected survival of an age- and sex-matched cohort estimated from the Australian Bureau of Statistics life tables for WA. Results: The OHCA patients who initially survived to 30-days experienced a modest reduction in long-term survival, with 84% (95% CI, 78–90) of patients surviving to 10-years relative to the age- and sex-matched general population. The 10-year relative survival increased from 76% (95% CI, 67–85) to 92% (95% CI, 84–100) between the first (1998−2007) and second (2008−2017) decade of our study. Conclusion: Relative long-term survival prospects for initial OHCA survivors are moderately lower than that of the general population, however these differences have reduced over time and may be approaching those of the general population.